2023
DOI: 10.1021/acsomega.2c07869
|View full text |Cite
|
Sign up to set email alerts
|

Formation of L10 Ordering in FeNi by Mechanical Alloying and Field-Assisted Heat Treatment: Synchrotron XRD Studies

Abstract: L10-ordered FeNi, tetrataenite, found naturally in meteorites is a predilection for next-generation rare-earth free permanent magnetic materials. However, the synthesis of this phase remains unattainable in an industrially relevant time frame due to the sluggish diffusion of Fe and Ni near the order–disorder temperature (593 K) of L10 FeNi. The present work describes the synthesis of ordered L10 FeNi from elemental Fe and Ni powders by mechanical alloying up to 12 h and subsequent heat treatment at 623 K for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the (100) superlattice peak of L1 0 FeNi coincides with the (311) fundamental peak of NiFe 2 O 4 . Spontaneous formation of NiFe 2 O 4 is possible during material handling and characterization. , Figures d and d show XRD patterns in the range of 42–45° of Figures a and a, respectively. An increase in the intensity of the (111) fundamental peak from the powder form to the laser-melted samples is observed, which can be attributed to the increase in the crystallinity of the sample during recrystallization.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the (100) superlattice peak of L1 0 FeNi coincides with the (311) fundamental peak of NiFe 2 O 4 . Spontaneous formation of NiFe 2 O 4 is possible during material handling and characterization. , Figures d and d show XRD patterns in the range of 42–45° of Figures a and a, respectively. An increase in the intensity of the (111) fundamental peak from the powder form to the laser-melted samples is observed, which can be attributed to the increase in the crystallinity of the sample during recrystallization.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe and Ni powders were mixed in an atomic ratio of 1:1 and mechanically alloyed using a dual-drive planetary ball mill. Our recent study has reported detailed work on the mechanical alloying of FeNi (50–50 atom %) alloy . Mechanically alloyed FeNi powder was mixed with camphor (Sigma-Aldrich, purity 96%) to make pellets of 15 mm diameter and ∼4 mm height at an applied pressure of ∼270 MPa for 5 min, using a uniaxial press (Kimaya Engineers, India).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations